2004
DOI: 10.1002/cncr.20269
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal soft tissue sarcomas

Abstract: BACKGROUNDThe objective of this study was to assess long‐term prognosis and patterns of failure in patients with retroperitoneal soft tissue sarcoma who underwent surgery with curative intent at a single institution. Several series of patients with retroperitoneal sarcoma were reported, providing widely variable data regarding local and distant failure.METHODSOverall, 167 consecutive patients who underwent surgery for retroperitoneal soft tissue sarcoma over a 20 year span at a single referral center were revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 160 publications
(44 citation statements)
references
References 24 publications
1
39
0
4
Order By: Relevance
“…Unfortunately, treatment of local recurrence is associated (in significant percentage of cases) with consecutive local recurrence. In group of patients presented in international literature, the predominated group consisted of patients operated primarily not due to recurrence [32, 54, 5658]. In our study we confirmed that treatment of primary retroperitoneal sarcomas is one of the major factor influencing prognosis ( on the basis of multivariate analysis with its limitation resulting from numerical amount of cases in analyzed group).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Unfortunately, treatment of local recurrence is associated (in significant percentage of cases) with consecutive local recurrence. In group of patients presented in international literature, the predominated group consisted of patients operated primarily not due to recurrence [32, 54, 5658]. In our study we confirmed that treatment of primary retroperitoneal sarcomas is one of the major factor influencing prognosis ( on the basis of multivariate analysis with its limitation resulting from numerical amount of cases in analyzed group).…”
Section: Discussionsupporting
confidence: 82%
“…However, series of publications were released with multiple sets of data regarding the treatment results of patients with this type of cancer. [18, 2332]. It seem like the best option for the longest distant survival rate is a radical resection during the primary surgery of retroperitoneal sarcoma [6, 18, 32, 33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liposarcoma is the most common histologic subtype of retroperitoneal sarcomas, with a higher local recurrence rate than non-liposarcomas (58% versus 22%) [6]. Even when tumor grade is taken into account, failure of disease control is mostly due to locoregional recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Complete excision with wide margins represents the mainstay of treatment, however even gross total resections are possible only in about 50% of the patients [2,3] because of the often locally advanced tumors which frequently already involve vital structures at time of diagnosis [3]. Even if gross total resection is possible, margins are typically narrow because of the normal tissue limitations [3,4] consequently the local failure rate after surgery alone remains high [5-7]. In accordance to extremity soft tissue sarcomas (STS), where randomized trials have demonstrated improved local control by the addition of radiation [8,9], considerable interest has been paid in the use of postoperative radiation approaches in retroperitoneal STS also.…”
Section: Introductionmentioning
confidence: 99%